2010
DOI: 10.1111/j.1473-2165.2010.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

UV irradiation‐induced zinc dissociation from commercial zinc oxide sunscreen and its action in human epidermal keratinocytes

Abstract: Zinc oxide (ZnO) is an active ingredient in sunscreen owing to its properties of broadly filtering the ultraviolet (UV) light spectrum and it is used to protect against the carcinogenic and photodamaging effects of solar radiation on the skin. This study investigated the dissociation of zinc (Zn(2+) ) from ZnO in commercial sunscreens under ultraviolet type B light (UVB) irradiation and assessed the cytotoxicity of Zn(2+) accumulation in human epidermal keratinocytes (HEK). Using Zn(2+) fluorescent microscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
(69 reference statements)
0
18
0
Order By: Relevance
“…Zinc oxide is another prime material candidate in the field of photoactive materials and is often discussed hand‐in‐hand with TiO 2 . Like TiO 2 , it falls into the category of semiconductor and has a broad spectrum adsorption with a bandgap of 3.2 eV,190 high refractive index of 1.95–2.10191 and the ability to absorb UVA and UVB 192. It has been studied heavily and even employed in numerous photoactive applications ranging from solar cells, photovoltaics to the most common UV‐filters in sunscreens.…”
Section: A Class Of High‐volume Production Nanomaterials: Photoactmentioning
confidence: 99%
See 2 more Smart Citations
“…Zinc oxide is another prime material candidate in the field of photoactive materials and is often discussed hand‐in‐hand with TiO 2 . Like TiO 2 , it falls into the category of semiconductor and has a broad spectrum adsorption with a bandgap of 3.2 eV,190 high refractive index of 1.95–2.10191 and the ability to absorb UVA and UVB 192. It has been studied heavily and even employed in numerous photoactive applications ranging from solar cells, photovoltaics to the most common UV‐filters in sunscreens.…”
Section: A Class Of High‐volume Production Nanomaterials: Photoactmentioning
confidence: 99%
“…Figure 201 reveals this mechanism in detail. ROS may accentuate ZnO's toxicity as shown by Chin et al202 Although ZnO‐induced ROS spikes have been well reported,192, 200, 201, 203–205 well planned dissolution studies must run parallel to cytotoxicity and ROS‐measurement studies in order to correctly attribute the source of ROS production to the nanoparticles or the ions.…”
Section: A Class Of High‐volume Production Nanomaterials: Photoactmentioning
confidence: 99%
See 1 more Smart Citation
“…ZnO NPs have been reported to elicit various adverse cellular effects, including genotoxicity 2 and cytotoxicity. 3 It has also been suggested that ultraviolet B irradiation causes increased dissociation of Zn 2+ from ZnO and that the consequent accumulation of free or labile Zn 2+ from sunscreen results in cytotoxicity and oxidative stress. 3 However, the mechanisms underlying these adverse effects are not fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…3 It has also been suggested that ultraviolet B irradiation causes increased dissociation of Zn 2+ from ZnO and that the consequent accumulation of free or labile Zn 2+ from sunscreen results in cytotoxicity and oxidative stress. 3 However, the mechanisms underlying these adverse effects are not fully characterized. Decreased collagen content in the skin due to oxidative stress at the site of application of ZnO has been reported.…”
Section: Introductionmentioning
confidence: 99%